2016
DOI: 10.1093/jcr/ucw049
|View full text |Cite
|
Sign up to set email alerts
|

Take It or Leave It: How Choosing versus Rejecting Alternatives Affects Information Processing

Abstract: People can make decisions by choosing or by rejecting alternatives. This research shows that changing a task from choice to rejection makes people more likely to rely on deliberative processing, what we label the task-type effect. To demonstrate this effect, we use a set of established decision biases that can be attenuated under deliberative processing. We show that changing a task from choice to rejection makes people express more consistent preferences between safe and risky options in the Asian disease pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 45 publications
3
33
0
Order By: Relevance
“…Task type (rejection vs. choice) is another factor affecting systematic processing (Sokolova & Krishna, 2016) and, thus, the role of partisanship in judgment. When making decisions, people can reject the less attractive alternatives (e.g., selecting which candidate they would rather not have as a president) or choose the more attractive ones (e.g., selecting which candidate they would rather have as a president).…”
Section: Why Does Partisanship Affect Voting Behavior and Attitudes?mentioning
confidence: 99%
See 1 more Smart Citation
“…Task type (rejection vs. choice) is another factor affecting systematic processing (Sokolova & Krishna, 2016) and, thus, the role of partisanship in judgment. When making decisions, people can reject the less attractive alternatives (e.g., selecting which candidate they would rather not have as a president) or choose the more attractive ones (e.g., selecting which candidate they would rather have as a president).…”
Section: Why Does Partisanship Affect Voting Behavior and Attitudes?mentioning
confidence: 99%
“…In turn, consideration of losses has been linked to greater visual attention (Hochman & Yechiam, 2011), and more rational decisions in risky choices (Yechiam & Hochman, 2013) and price evaluations (Chatterjee, Heath, Milberg, & France, 2000). With loss considerations being more prominent in rejection, rejection decisions lead to more systematic processing compared to choice decisions (as shown by Sokolova & Krishna, 2016). Applied to the context of partisan judgments, this implies that rejecting the less attractive candidate (vs. choosing the more attractive one) may lead people to become less reliant on partisan cues when voting.…”
Section: Why Does Partisanship Affect Voting Behavior and Attitudes?mentioning
confidence: 99%
“…Research has documented various downstream consequences to the screening process (e.g., Chakravarti, Janiszewski, & Ülkümen, 2006;Nedungadi, 1990). Although past research has found that excluding may result in a consideration set more consistent with one's preferences (Kogut, 2011;Sokolova & Krishna, 2016) and greater weight placed on ethical attributes (Irwin & Naylor, 2009), these studies do not make direct claims about consideration set quality. Testing quality directly, studies have not found a difference in consideration set quality as a function of strategy (Levin et al, 2000).…”
Section: Downstream Consequences Of Consideration Set Construction mentioning
confidence: 99%
“…Related research has used the terms "accept," "select," "choose," or "retain" versus "reject" or "eliminate." However, these terms are generally used to refer to a choice between two (or three) options in the choice phase and not to the consideration set construction phase of the decision process (e.g.,Chernev, 2009;Meloy & Russo, 2004;Shafir, 1993;Sokolova & Krishna, 2016;Wedell, 1997; but seeOrdóñez et al, 1999 for an exception).…”
mentioning
confidence: 99%
“…The impact of different decision tasks (i.e., choice vs. rejection) on people’s behavior has been investigated in various fields, including psychology (Meloy and Russo 2004), retailing (Nagpal, Lei, and Khare 2015), marketing (Laran and Wilcox 2011; C. W. Park, Jun, and Macinnis 2000; Sokolova and Krishna 2016), and tourism (J. Kim et al 2019).…”
mentioning
confidence: 99%